(NaZBUKA ZWEZDNOGO NEBA (B/s - (NdANLOP(B, (NsTORMs; (N~ARUGIN(B, (Nw(B.(Nm(B.s (NPERs; (NkOZENKO(B, (Na(B.(Nw(B.s (NREDs ((NmOSKWA (B:s (NmIR(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 226-228s
(NpREDM(B. (NUKAZ(B.: (NS(B. 230-235s
Keywords: 9